Nipah Virus Transmission in a Hamster Model - de Wit, Emmie; Bushmaker, Trenton; Scott, Dana; Feldmann, Heinz; Munster, Vincent J. (PLOS Neglected Tropical Diseases, 2011)
Author Summary Understanding how viruses are transmitted plays an important role in our ability to intervene in virus outbreaks. Over the last decade, Nipah virus has caused multiple outbreaks in Malaysia, India and especially Bangladesh. Fruit bats form the natural reservoir for Nipah virus; from the bats the virus is introduced into the human population, either directly or via an intermediate host. Epidemiological data suggest that upon introduction into the human population the virus has the ability to spread from person-to-person. We performed experimental studies in a hamster model to investigate if we could mimic human-to-human transmission and to determine the route of transmission through which Nipah virus spread between people. We discovered that Nipah virus-infected hamsters predominantly shed virus via excretions from the nose and lungs. In transmission experiments, we showed that Nipah virus is efficiently transmitted via direct contact. Fomite transmission was inefficient and transmission via aerosols did not occur. The elucidation of the mode of Nipah virus transmission has important public health implications because it allows a targeted and experiment-based assessment of intervention strategies and surveillance for emerging Nipah virus strains better adapted to human-to-human transmission.